(3bUjOI ojPcQ ajgG GdEeGe CMeO Hf MfHds - (3jMji Hf jhSa Hf jMji GdCfUGQj, GdUQUQj, LeGd GdOjf CHh RcQjG,J (B656 (3g` s
(3ChdgG (B:s
(3TQO Yf Yjfj GdcQi Wja SQi ef Ce YeQ aj ZjGgH GdOLG s
(3BNQgG (B:s
(3adSJ ef GdNWH Gdede HNGFa hCfJ Ydi cd GdTOGFO dj hdj JeJ HYhf Gddg hMSf Jhajbg hGdMeO QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B177 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B236 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B523s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdOhdI (B- (3HQdjf (B- (3CdeGfjG GdZQHjI (B(15517) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs